Sistem Pengendali On-Off Lampu dan Motor Servo sebagai Penggerak Gerendel Pintu Berbasis Internet Of Things (IoT) - Ramdan Ramdan; Lasmadi Lasmadi; Paulus Setiawan (Aviation Electronics, Information Technology, Telecommunications, Electricals, Controls (AVITEC), 2022)
The application of Internet of Things (IoT) technology will be one of the technologies that complements all fields along with the increasing use of smartphones. The purpose of this research is to design an on-off control system for lights and servo motors as door latch actuator based on IoT. The designed system can give commands on/off the lamp or door latch actuator and display the on/off indicators through an application on an Android smartphone. The system is designed using a Wemos D1 mini microcontroller as a processor, light sensor, infrared sensor, relay, servo motor, and RemoteXY app. Based on the test results, the system design has been successfully implemented and can be operated as an on-off controller via the internet with an Android smartphone. For each test performed, the system managed to provide an output that matches the given control input. The response time (delay) of the relay when on or off the lamp about 34,83 ms while the response time of the servo motor when opening and closing the latch takes about 38,93 ms. The notification shown corresponds to the state of the lamp and the state of the latch.